New insights to the taxonomy of Rhagodes eylandti (Walter, 1889): A remarkable sexually dimorphic species (Solifugae: Rhagodidae) - Maddahi, Hassan; Aliabadian, Mansour; Moradmand, Majid; Mirshamsi, Omid (Zootaxa, 2019)
The taxonomy of the widespread camel spider, Rhagodes eylandti (Walter, 1889), is herein updated and revised by proposing three nominal taxa as its junior synonyms. These are based on data from males of two taxa, Rhagodes melanopygus nigricans Birula, 1905 and R. plumbescens (Walter, 1889), and a female of R. melanochaetus Heymons, 1902. Consequently, both sexes of R. eylandti are re-described and the validity of their morphological diagnostic characters is evaluated. Detailed morphological and morphometrical characters, as well as data on sexual dimorphism and intraspecific variations, are provided. The illustrations of type material are given for the first time. Moreover, a distribution map and ecological notes are presented.